Fair and fit resource allocation algorithm for network-controlled device-to-device (D2D) communication / Yusmardiah Yusuf, Darmawaty Mohd. Ali and Roslina Mohamad - Yusuf, Yusmardiah; Mohd. Ali, Darmawaty; Mohamad, Roslina (Universiti Teknologi MARA, 2021)
Device-to-device (D2D) communication is a promising new feature for next generation cellular networks. However, enabling D2D communications in a cellular network presents a challenge in resource allocation due to the spectrum sharing with the cellular users which cause interference. The previous works in D2D resource allocation focused on improving the throughput of the overall network while completely ignoring the fairness aspect. Therefore, such issues can be managed if radio resource is assigned intelligently with the coordination from the eNodeB (eNB). In this paper, a Fair and Fit Resource Allocation (FFRA) algorithm is proposed which exploits the path loss experienced by the potential D2D user equipments (UEs) when choosing the communication path. Then, D2D UEs were scheduled using proportional fair (PF) packet scheduler. PF scheduler was developed to improved on the throughput and guarantees fairness among the flows. The FFRA scheme was applied in two communication scenarios, namely in a single D2D UE and multiple D2D UEs. OMNET++ discrete event simulator together with INET and SimuLTE framework are the platforms used to conduct the simulation. Simulation results show that, the FFRA algorithm outperform Max C/I and RR with 32.73% and 38.67% increased in total throughput while achieving excellent performance of fairness as the number of D2D UEs increases in the networks. In addition, the FFRA algorithm contributes to the lowest delay and packet loss amongst the algorithms.